Role of Actors in Covid-19 Control in West Nusa Tenggara Province - Utama, Lalu Satria; Syaefullah, Syaefullah; Rahman, Abdul; Yuliani, Dwi Putri; Marzuki, Marzuki (PT. Riset Press International, 2024)
The study has purpose to analyze the role of actors in the social representation of Covid-19 control. The study uses a mixed method with an explanatory sequential design. The results shows that there is a positive influence on the role of actors on the discipline of health protocols in controlling Covid-19 in West Nusa Tenggara (NTB), each pentahelix actor participates well. Higher education as a consulting actor provides input, views, and academic legitimacy. Academics criticize policies scientifically so that they can be accepted and have an impact as an alternative problem’s solving. Pharmaceuticals accelerate the production of domestic drug raw materials and to fulfill the realization of national drug raw material independence. BPBD NTB coordinates with the Indonesian Red Cross provides basic disaster management training for government officials, communities, businesses, non-governmental organizations, and other stakeholders. Community helps the government's task of reducing any potential threat of threatening disasters.